Ghrelin mediates exercise endurance and the feeding response post-exercise - Bharath K. Mani; Carlos M. Castorena; Sherri Osborne-Lawrence; Prasanna Vijayaraghavan; Nathan P. Metzger; Joel K. Elmquist; Jeffrey M. Zigman (Elsevier, 2018)
Objective: Exercise training has several well-established health benefits, including many related to body weight, appetite control, and blood glucose homeostasis. However, the molecular mechanisms and, in particular, the hormonal systems that mediate and integrate these beneficial effects are poorly understood. In the current study, we aimed to investigate the role of the hormone ghrelin and its receptor, the growth hormone secretagogue receptor (GHSR; ghrelin receptor), in mediating the effects of exercise on food intake and blood glucose following exercise as well as in regulating exercise endurance capacity. Methods: We used two mouse models of treadmill running to characterize the changes in plasma ghrelin with exercise. We also assessed the role of the ghrelin system to influence food intake and blood glucose after exercise, exercise endurance, and parameters potentially linked to responses to exercise. Mice lacking GHSRs (GHSR-null mice) and wild-type littermates were studied. Results: An acute bout of exercise transiently elevated plasma acyl-ghrelin. Without the action of this increased ghrelin on GHSRs (as in GHSR-null mice), high intensity interval exercise markedly reduced food intake compared to control mice. The effect of exercise to acutely raise blood glucose remained unmodified in GHSR-null mice. Exercise-induced increases in plasma ghrelin positively correlated with endurance capacity, and time to exhaustion was reduced in GHSR-null mice as compared to wild-type littermates. In an effort to mechanistically explain their reduced exercise endurance, exercised GHSR-null mice exhibited an abrogated sympathoadrenal response, lower overall insulin-like growth factor-1 levels, and altered glycogen utilization. Conclusions: Exercise transiently increases plasma ghrelin. GHSR-null mice exhibit decreased food intake following high intensity interval exercise and decreased endurance when submitted to an exercise endurance protocol. These data suggest that an intact ghrelin system limits the capacity of exercise to restrict food intake following exercise, although it enhances exercise endurance. Keywords: GHSR, Ghrelin, Exercise, Treadmill, Endurance, Food intake